A Serial Mediation Model on Trait Emotional Intelligence, Basic Psychological Needs, and Academic Motivation as Antecedents of Student Engagement - Wei Mun Chin; Nor Aniza Ahmad; Ismi Arif Ismail; Siti Noormi Alias; Alia Sarah Asri (SAGE Open)
Promoting student engagement has always been a challenging endeavor, and the global pandemic has added to the complexity by disrupting traditional classroom settings. Consequently, it has become vital to investigate and address the challenges that students face in environments with academic disruption. In this study, Structural Equation Modeling was applied to analyze the collected data from a cross-sectional sample of 461 participants through the proportionate stratified random sampling method during the global pandemic at a selected Malaysian public research university. The researchers investigated the relationship between trait emotional intelligence, basic psychological needs, academic motivation, and student engagement, including the potential serial mediation of basic psychological needs and academic motivation in this relationship. The results indicated that trait emotional intelligence, basic psychological needs, and academic motivation were significant positive predictors of student engagement. Trait emotional intelligence was also a positive and significant predictor of basic psychological needs but was insignificant regarding academic motivation. On the other hand, basic psychological needs was a significant positive predictor of academic motivation. Basic psychological needs and academic motivation partially mediated the relationship between trait emotional intelligence and student engagement. The findings suggest that undergraduate students with higher levels of trait emotional intelligence, basic psychological needs, and academic motivation would have better student engagement, suggesting the need for further research related to the supportive environment for students in modern classroom settings.